Attachment Ventilation Theory - Li, Angui; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This open access book systematically summarizes the current research progress of attachment ventilation, covering vertical wall attachment, column attachment, and adaptive attachment ventilation. Attachment ventilation is a high-performance ventilation mode that was first proposed by the author, Prof. Angui Li 20 years ago. Now it has been widely used in office spaces, subway stations, high-speed railway stations, international airport terminals, and other large spaces. This book introduces attachment ventilation in detail to eliminate the cooling/heating load of the occupied zone and provide an expected environment for the air-conditioned zone. Attachment ventilation combines the advantages of traditional mixed ventilation and displacement ventilation. This book consists of six chapters, covering a series of airflow patterns, mechanisms, parameter correlations, and attachment ventilation design methods. It is helpful for HVAC engineers to design attachment ventilation effectively.
Cooking history and development of kitchen appliances -- Kitchen ventilation requirements -- Pollutions of cooking oil fume and health risks -- Thermal comfort in kitchen -- Basis to calculate exhaust airflow rate -- Design of kitchen ventilation -- High performance kitchen ventilation -- Stack effects of kitchen exhaust shaft in high-rise building -- Case study and design of kitchen ventilation.
Keywords: Buildings -- Environmental engineering; Fluid mechanics; Building information modeling; Computer simulation; Building Physics, HVAC; Engineering Fluid Dynamics; Building Information Modeling; Computer Modelling